Statistical Analysis of Factors Affecting Poverty in West Nusa Tenggara Province 2017-2021 - I Kadek Ago Budiarta; Putu Karismawan; Ida Ayu Putri Suprapti (Tinta Emas Publisher, 2023)
The high level of poverty in West Nusa Tenggara shows that the economic development process has not been able to improve community welfare evenly. Thus, it is necessary to analyze the factors that influence poverty in an effort to overcome the problem of poverty. This research aims to determine the influence of education, GRDP and Regency/City Unemployment partially or simultaneously on poverty in West Nusa Tenggara Province in 2017-2021. This test was carried out in 10 districts/cities in NTB Province with the observation year being 2017-2021. This research uses a quantitative approach and associative methods. Data collection was carried out using the documentation method, literature study and then analyzed using panel data regression analysis using the Random Effect Model (REM) approach using Eviews 10 software. The results of this research show that education has a significant and negative effect on poverty. GRDP has an insignificant and negative effect on poverty and unemployment has an insignificant and negative effect on poverty. Furthermore, education, GDP and unemployment simultaneously have a significant effect on poverty. The implication of this research is to provide information about factors that can influence poverty and for the government it can be used as consideration regarding efforts to reduce poverty in West Nusa Tenggara Province.